Avaratra gen. nov. (Hemiptera: Fulgoromorpha: Flatidae) from northern Madagascar endemism centre - Świerczewski, Dariusz; Stroiński, Adam (Zootaxa, 2022)
A new monospecific genus of flatid planthoppers (Hemiptera: Fulgoromorpha: Flatidae), Avaratra gen. nov., is described for Avaratra spinifemora sp. nov. (type species) from the island of Madagascar. Habitus, male and female external and internal genital structures of the new species are illustrated. Avaratra spinifemora gen. et sp. nov. is endemic to Madagascar and probably represent a species specialized to dry costal forest, the vegetation widely distributed in Madagascar, gradually extending with the climate change. Taking into account a few data and poor collecting in these areas, particularly for planthoppers, it is possible that the species occurs in other similar places along the west northern coast.